Social cognitive theory-based health promotion in primary care practice: A scoping review. Issue 4 (April 2023) - Islam, Kazi Faria; Awal, Abdul; Mazumder, Hoimonty; Munni, Ummi Rukaiya; Majumder, Koushik; Afroz, Kohinoor; Tabassum, Mustari Nailah; Hossain, M. Mahbub
Abstract: Background: Using a theoretical perspective to guide research design and implementation can result in a coherent preventative intervention model. Among theoretical frameworks, Bandura's Social Cognitive Theory (SCT) is particularly useful for studies focused on behavior change in health promotion research. Objective: This scoping review explored and summarized the current evidence on health promotion interventions that integrated constructs of Social Cognitive Theory and the outcome of those interventions in primary care settings. Method: ology: We conducted this scoping review using the PRISMA scoping review guidelines; we reviewed articles from five electronic databases and additional sources that were peer-reviewed journal articles reporting interventions applying SCT constructs and synthesized the outcomes following the interventions. Results: Among 849 retrieved from multiple sources, 39 articles met our eligibility criteria. Most studies (n = 19) were conducted in the United States. Twenty-six studies followed a randomized control trial design. Most studies (n = 26) recruited participants utilizing the primary care network. All 39 studies mentioned "self-efficacy" as the most utilized construct of SCT to determine how behavior change operates, followed by "observational learning" through role models. Twenty-three studies integrated individual (face-to-face) or peered group-based counseling-training programs; eight interventions used telephonic health coaching by a specialist; eight studies used audio-visual mediums. All included studies reported positive health outcomes following the intervention, including increased self-reported moderate-to-vigorous physical activity, increased Knowledge of dietary intake, high-risk behaviors such as STIs transmission, adapting to a healthy lifestyle, and adherence to post-transplant medication. Conclusion: Current evidence suggests that SCT-based interventions positively impact health outcomes and intervention effectiveness. The results of this study indicate the importance of incorporating and assessing several conceptual structures of behavioral theories when planning any primary care health promotion practice.